2003
DOI: 10.1046/j.1442-2018.2003.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining characteristics of expertise in Japanese clinical nursing using the Delphi technique

Abstract: A four-round Delphi technique was conducted on 127 experienced Japanese nurses to develop a consensus of opinion on the defining characteristics underlying expertise, and the prime requirements for the development of expertise in clinical nursing. Sixteen statements identified as the prime defining characteristics underlying expertise indicated that experienced Japanese nurses' picture of expertise is general, comprehensive and focused on task expertise. Four prime requirements for the development of expertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…(); (7) McHugh and Lake (); (8) Morrison and Symes (); (9) Naumanen‐Tuomela (); (10) Nojima et al. (); (11) Cutcliffe (); (12) Johnston and Smith (); (13) Brykczynski (); (14) Bonner (); (15) Conway (); and (16) Bobay et al. ().…”
Section: Resultsmentioning
confidence: 99%
“…(); (7) McHugh and Lake (); (8) Morrison and Symes (); (9) Naumanen‐Tuomela (); (10) Nojima et al. (); (11) Cutcliffe (); (12) Johnston and Smith (); (13) Brykczynski (); (14) Bonner (); (15) Conway (); and (16) Bobay et al. ().…”
Section: Resultsmentioning
confidence: 99%
“…Although findings have not been consistent in all settings (Hoffman et al 2009), expert nurses were seen to collect and cluster fewer cues with high diagnostic accuracy and on a wider range of aspects of the patient's presenting symptoms focusing on these that are relevant to the hypothesis made (Aitken 2003). Novice nurses collected greater number of cues, concentrated only on the presenting symptoms of the patient and were less proactive in collecting relevant information and anticipating problems (Nojima et al 2003), because of their inability to discriminate between salient and non-salient cues. To understand better how nurses collect and use cues to make decisions, this study was designed to answer the following questions: 1 What cues do novice and expert critical care nurses cluster together to make a decision about the management of patients who wean off mechanical ventilation?…”
Section: Introductionmentioning
confidence: 94%
“…Novice nurses collected greater number of cues, concentrated only on the presenting symptoms of the patient and were less proactive in collecting relevant information and anticipating problems (Nojima et al . ), because of their inability to discriminate between salient and non‐salient cues. To understand better how nurses collect and use cues to make decisions, this study was designed to answer the following questions: What cues do novice and expert critical care nurses cluster together to make a decision about the management of patients who wean off mechanical ventilation? What strategies do novice and expert critical care nurses use to evaluate the cues presented by the patient when making decisions about the management of patients who wean off mechanical ventilation? Are there any differences between novice and expert critical care nurses in the use of cues when they make decisions about the management of patients who wean off mechanical ventilation? …”
Section: Introductionmentioning
confidence: 99%
“…Expert nurses were seen to collect information on a wide range of aspects in addition to the patients' presenting symptoms and illness when collecting cues for a particular problem, while novice nurses tended to concentrate on the presenting symptoms only (White, Nativio, Kobert and Engberg, 1992). In contrast, a study by Hanneman (1996) and a study by Nojima, Tomikawa, Makabe and Synder (2003) found that expert nurses' assessment was found to be more focused than that of novice nurses, concentrating on a smaller range of cues.…”
Section: Introductionmentioning
confidence: 95%